Query Rewriting for Nested Navigational Queries over Property Graphs - Löhnert, Bianca; Augsten, Nikolaus; Okulmus, Cem; Ortiz, Magdalena (Proceedings of the 38th International Workshop on Description Logics (DL 2025), Opole, Poland, September 3-6, 2025.)

Ressourcenräume: Seerecht, Geopolitik und Wissenschaftsdiplomatie zwischen den Seychellen, Frankreich und der Bundesrepublik Deutschland um 1980 - Kunkel, Sönke; Sackel, Johanna (Räume in der Internationalen Geschichte)

Rechnen mit Beziehungen - operative Beziehungen erkennen, beschreiben und nutzen. Entwicklung einer digitalbasierten Lernumgebung mit der App Rechenfeld - Dettelbach, Andrea (Beiträge zum Mathematikunterricht 2025)

Normatives Modellieren im Kontext des Klimawandels – wie viel CO2 stoßen Lebensmittel aus? - Gildehaus, Lara; Liebendörfer, Michael; Hüsing, Sven; Gottschalk, Rebecca; Strauß, Franzisca (Realitätsbezüge im Mathematikunterricht)

Konstruktionistisches Geometrielernen durch epistemisches Programmieren in Scratch - Stoppel, Hannes; Hüsing, Sven (Beiträge zum Mathematikunterricht; 58)

Empowering Students to Gain Insights within Data Exploration Projects in the Classroom - Using, Modifying, and Creating Data Moves through a Scaffolded Use of Digital Tools - Hüsing, Sven; Podworny, Susanne (Symposium on integrating AI and data science into school education across disciplines)

Using SysML as a Modelling Language for Dataspaces - Kulkarni, Pranav Jayant; Zerbin, Julian; Koldewey, Christian; Bernijazov, Ruslan; Dumitrescu, Roman (2024 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))
Utilizing data is crucial for economic success, but a lack of interoperability and concerns about the misuse of ones own data are hindering the cross-organizational use of data. Dataspaces provide the infrastructure necessary to integrate heterogeneous data sources within an organization or ecosystem, enabling seamless data interaction and interoperability. In addition, data spaces strengthen data sovereignty through their decentralized nature, which enables organizations to effectively control and manage their data. However, challenges persist in managing the complexity and dynamic nature of dataspaces, requiring significant resources and technical expertise. The decentralized nature leads to a large and diverse number of stakeholders, who need to agree on the use and scope of a dataspace. Modeling is a common approach to cope with technical complexity and heterogeneous stakeholders. In this paper, we propose a version of SysML and a corresponding method that focus on the modelling of data spaces. We provide a dataspace modelling method to unify the understanding of dataspaces and scope among all stakeholders to simplify the design and development process.
Keywords: Dataspaces; Modelling; SysML; Gaia-X; System Specification

Igniting Knowledge Management for Assistance Systems in Maintenance: A Method for Knowledge Gathering - Skolik, Alexander Marcus; zur Heiden, Philipp; Donner, Johannes Aurelius Tamino; Priefer, Jennifer (ECIS 2025 Proceedings)

Geschlechterstereotype Selbstdarstellungen junger Frauen in der Ausbildungsvorbereitung - Schotten, Sarah Theresa; Otto, Franziska; Kremer, H.-Hugo (Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2025)

The Influence of Mathematical Achievement on the Development of Intuitive Probabilistic Reasoning in Lower Secondary School Students - Wiemann, Leon; Schroeder, Sascha; Halverscheid, Stefan (Proceedings of the 48th Conference of the International Group for the Psychology of Mathematics Eduction: Research Reports, Vol. 2)

Schmidt modes carrying orbital angular momentum generated by cascaded systems pumped with Laguerre–Gaussian beams - Scharwald, Dennis; Gehse, Lucas; Sharapova, Polina (APL Photonics)
Orbital angular momentum (OAM) modes are an important resource used in various branches of quantum science and technology due to their unique helical structure and countably infinite basis. Generating light that simultaneously carries high-order orbital angular momenta and exhibits quantum correlations is a challenging task. In this work, we present a theoretical approach to the generation of correlated Schmidt modes carrying OAM via parametric down-conversion (PDC) in cascaded nonlinear systems (nonlinear interferometers) pumped by Laguerre–Gaussian beams. We demonstrate how the number of generated modes and their population can be controlled by varying the pump parameters, the gain of the PDC process, and the distance between the crystals. We investigate the angular displacement measurement uncertainty of these interferometers and demonstrate that it can overcome the classical shot noise limit.

Die Konstruktion eines Fragebogens zur Messung der probabilistischen Intuition von Schüler*innen der Sekundarstufe I - Wiemann, Leon (Beiträge zum Mathematikunterricht 2025. 58. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Phononic crystallography of fibre-reinforced polymers using broadband acoustic waves - Wippermann, Mareen; Claes, Leander (2025 International Congress on Ultrasonics)

Experimentelle und numerische Analyse des Fließverhaltens von hochviskosen Wärmeleitstoffen im Fertigungsprozess - Gilich, Julian; Meschut, Gerson; Gröger, Benjamin; Wiebicke, Felix; Koch, Ilja; Gude, Maik (25. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

The spread of the English language – Das Englische als globales Phänomen (Grundschule Englisch)

Flammentemperaturmessung mittels thermischer Trägheit von Thermoelementen – Dynamische Methode (Poster) - Wortmeier, Andreas; Gonchikzhapov, Munko; Kasper, Tina

An applied noise model for low-loss EELS maps - Zietlow, Christian; Lindner, Jörg (Ultramicroscopy)

Think Globally, Attend Locally - Turhan, Anni-Yasmin (Künstliche Intell.)

Forschungs- und Spannungsfeld Immaterielles Kulturerbe. Erfahrungen und Erkenntnisse im Forschungsprojekt „Tradition im Wandel – Schützenwesen in Westfalen“ (2016–2024) - Leineweber, Jonas (Rheinisch-Westfälische Zeitschrift für Volkskunde)

An applied noise model for scintillation-based CCD detectors in transmission electron microscopy. - Zietlow, Christian; Lindner, Jörg (Sci Rep)